"Life Is Not Mere Living but Living in Health" - An Overview of Rural Health Practice - Ravishekar N Hiremath; Venkatesh Govindasamy; Sandeep Bhalla; Sandhya Ghodke; Renuka Kunte; Shubhralok Sinha (Medsci Publications, 2013)
India is home to one-sixth of the world's population. It has shown rapid development in recent years.  People who live in rural areas experience many health disadvantages including inequitable access to health services in comparison with urban counterparts. So providing health care to the rural India is a biggest challenge. Evidence based rural health practices thus come to play a vital role in such scenario. This article is an attempt to give insight to the rural health practices, health care workforce and modes of health care services provision in rural India.